Compression load-carrying capacity of 3D-integrated weft-knitted spacer composites. (May 2019) - Hassanzadeh, Sanaz; Hasani, Hossein; Zarrebini, Mohammad
Recent developments in composite manufacturing have been resulted in formation of newly-known 3D integrated weft-knitted fabrics which can be used as the composites' reinforcing materials. In this paper, the compression-resistivity of 3D composite panels reinforced with these newly designed 3D textile-preforms from E-glass fibers has been studied. Following this research, the composites mechanical functionality under flatwise and edgewise compression loadings was evaluated. Using VIP method, three groups of glass/epoxy composite with different core thicknesses and structural geometries were prepared. It was concluded that the compressive strength of the flat-wisely loaded samples would significantly decrease by increasing the thickness. Moreover, changing the composites' geometrical shape leads to some changes in failure mode; in this regard, the produced single-decker U-shaped panels only suffer from the pure buckling failure, while the double-decker U-shaped panel failed due to a combination of facing bending stress, core shear stress, and buckling failure. Thickness changes are not as effective as structural geometry changes on the panels' compress-resistivity under edgewise compression. As compared with the conventional 3D woven sandwich composites, it was approved that mechanical functionality of the produced 3D integrated weft-knitted spacer panels is completely improved so that they can be considered as good alternatives especially in building constructions.